Cultural Aspects of Compulsive Buying in Emerging and Developed Economies: a Cross Cultural Study in Compulsive Buying - Horváth, Csilla; Adigüzel Feray; Herk, Hester van (Organizations and Markets in Emerging Economies, 2013)
Although several studies focused on understanding of compulsive buying in developed countries, this phenomenon remains understudied in other parts of the world. This is rather surprising since there is an increasing interest in understanding shopping behavior of consumers in emergent markets due to the growing importance of these markets. The main reason for the limited attention to compulsive buying in emerging countries is the lack of cross-culturally validated scales. In response to these calls, this paper tests measurement invariance of two prominent compulsive buying scales – the Compulsive Buying Scale (CBS) and the Compulsive Buying Index (CBI) in Western (Spain and the Netherlands) and emerging (Russia and Turkey) economies. In case of lack of invariance the reasons in terms of socio-cultural factors and country conditions are explained. The results establish the partial measurement invariance of the CBI but not the CBS. So, to study the antecedents and consequences of compulsive buying in cross-cultural contexts, the CBI is sufficient. The varying credit card ownership and usage, and different gender roles of women across countries appear to be the main reasons for lack of measurement invariance of the CBS. The percentages of compulsive buyers in emerging countries are lower than those in developed countries.